Dissolved Organic Matter: Biogeochemistry, Dynamics, and Environmental Significance in Soils - Bolan, Nanthi S; Adriano, Domy C; Kunhikrishnan, Anitha; James, Trevor; McDowell, Richard; Senesi, Nicola (Advances in agronomy, 2011)
Dissolved organic matter (DOM) is defined as the organic matter fraction in solution that passes through a 0.45 μm filter. Although DOM is ubiquitous in terrestrial and aquatic ecosystems, it represents only a small proportion of the total organic matter in soil. However, DOM, being the most mobile and actively cycling organic matter fraction, influences a spectrum of biogeochemical processes in the aquatic and terrestrial environments. Biological fixation of atmospheric CO₂ during photosynthesis by higher plants is the primary driver of global carbon cycle. A major portion of the carbon in organic matter in the aquatic environment is derived from the transport of carbon produced in the terrestrial environment. However, much of the terrestrially produced DOM is consumed by microbes, photo degraded, or adsorbed in soils and sediments as it passes to the ocean. The majority of DOM in terrestrial and aquatic environments is ultimately returned to atmosphere as CO₂ through microbial respiration, thereby renewing the atmospheric CO₂ reserve for photosynthesis. Dissolved organic matter plays a significant role in influencing the dynamics and interactions of nutrients and contaminants in soils and microbial functions, thereby serving as a sensitive indicator of shifts in ecological processes. This chapter aims to highlight knowledge on the production of DOM in soils under different management regimes, identify its sources and sinks, and integrate its dynamics with various soil processes. Understanding the significance of DOM in soil processes can enhance development of strategies to mitigate DOM-induced environmental impacts. This review encourages greater interactions between terrestrial and aquatic biogeochemists and ecologists, which is essential for unraveling the fundamental biogeochemical processes involved in the synthesis of DOM in terrestrial ecosystem, its subsequent transport to aquatic ecosystem, and its role in environmental sustainability, buffering of nutrients and pollutants (metal(loid)s and organics), and the net effect on the global carbon cycle.